Developmental trajectories of gyrification and sulcal morphometrics in children and adolescents at high familial risk for bipolar disorder or schizophrenia - Poortman, Simon R; Jamarík, Jakub; Ten Harmsen van der Beek, Louise; Setiaman, Nikita; Hillegers, Manon H J; Barendse, Marjolein E A; van Haren, Neeltje E M (Developmental cognitive neuroscience, 2025)
Offspring of parents with severe mental illness are at increased risk of developing psychopathology. Identifying endophenotypic markers in high-familial-risk individuals can aid in early detection and inform development of prevention strategies. Using generalized additive mixed models, we compared age trajectories of gyrification index (GI) and sulcal morphometric measures (i.e., sulcal depth, length and width) between individuals at familial risk for bipolar disorder or schizophrenia and controls. 300 T1-weighted MRI scans were obtained of 187 individuals (53 % female, age range: 8-23 years) at familial risk for bipolar disorder (n = 80, n families=55) or schizophrenia (n = 53, n families=36) and controls (n = 54, n families=33). 113 individuals underwent two scans. Globally, GI, sulcal depth and sulcal length decreased significantly with age, and sulcal width increased significantly with age in a (near-)linear manner. There were no differences between groups in age trajectories or mean values of gyrification or any of the sulcal measures. These findings suggest that, on average, young individuals at familial risk for bipolar disorder or schizophrenia have preserved developmental patterns of gyrification and sulcal morphometrics during childhood and adolescence.
Keywords: Bipolar Disorder; Magnetic Resonance Imaging; Bipolar disorder; Female; bipolární porucha; dítě; mladý dospělý; ženské pohlaví; Adolescent; lidé; magnetická rezonanční tomografie; Longitudinal; schizofrenie; High familial risk; Gyrification; Male; Child of Impaired Parents; Young Adult; Schizophrenia; mozková kůra; Cerebral Cortex; Child; mužské pohlaví; dítě postižených rodičů; mladiství; Offspring; Humans